Post-procedure sedation and apnea linked to ion channel variant: a case report on dexmedetomidine-propofol interaction - Stocco, Gabriele; Galletti, Anna; Lucafò, Marianna; Giurici, Nagua; Curci, Debora; Solidoro, Sara; Kiren, Valentina; Bianco, Anna Monica; Barbi, Egidio; D’Adamo, Pio (Frontiers in Pharmacology, 2025)
We report a case of post-awakening recurrent episodes of spontaneous re-sedation and apnea with severe desaturation after procedural sedation with dexmedetomidine and propofol in a leukemic adolescent with an ionic channel variant. The mutation is located in the 3′-UTR regulatory region of SCN9A. We speculate that this variant may affect the stability of the mRNA, making the patient more susceptible to the combined effects of propofol and dexmedetomidine. This is the first pediatric report of late onset re-sedation with apnoea after combined sedation with propofol and dexmedetomidine highlighting the risk of adverse events in selected patients with a genetic increased susceptibility. If validated by further studies, pharmacogenetic testing may be implemented to provide personalized therapies in patients needing anesthesia.